Lignin-Based Polymeric Hydrogel Materials for the Removal of Copper Ions from Water - Roa-Ruiz, K; Oyarce-Riveros, E; Boulett-Neira, A; Boulett-Neira, A (John Wiley and Sons Inc, 2025)
Sodium 4-styrene sulfonate was polymerized with lignosulfonic acid (LS) to obtain adsorbents for copper ions. The percentage of LS was varied, and the obtained systems were characterized by Fourier-transformed infrared spectroscopy, thermogravimetry, and scanning electron microscopy. Chemical composition, adequate thermostability, and a porous morphology with a pore size distribution favoring Cu(II) adsorption were corroborated. In hydration studies, all systems have a swelling capacity higher than 2000% at 60.0 min, whereas systems prepared with 20.0 and 30.0 wt.% of LS adsorb a higher amount of water owing to the high availability of polar sites. In contrast, adsorption studies were able to capture 25.1 mg of Cu(II) per g of adsorbent (prepared with 30.0 wt.% LS). The data obtained were fitted to a pseudo-first-order kinetics and Freundlich isotherm model, indicating a heterogeneous adsorbent surface. The thermodynamic parameters demonstrated the affinity between the active sites of the solid and Cu(II) in solution. It was determined that the adsorption mechanism is governed by the concentration gradient of Cu(II) at the interface (adsorbent–solution) and interactions of ion exchange and complexation types. Finally, the reuse of the bio-based adsorbent was achieved in consecutive adsorption–desorption cycles in up to four cycles. © 2024 Wiley Periodicals LLC.